Hyperosmolar therapy in pediatric traumatic brain injury: a systematic review - Marta Rodrigues; Marta Grilo; Maria João Baptista (Hygeia Press di Corridori Marinella, 2023)
Background: Traumatic brain injury (TBI) is a prominent reason for morbidity and mortality in children. The use of hyperosmolar therapy to manage increased intracranial pressure (ICP) is portrayed in pediatric guidelines; however, there still remains some debate regarding which option to select. The aim of this systematic review was to assess which hyperosmolar therapy - mannitol or hypertonic saline (HTS) - is more effective in terms of lowering ICP and having better outcomes in treating children with TBI. Methods: A literature search was conducted using MEDLINE (through PubMed), Scopus, and Web of Science. This review included 6 retrospective and prospective studies comparing the use of mannitol and HTS in pediatric patients with TBI.  Results: HTS was the most frequently described hyperosmolar agent, obtaining better results in managing ICP, cerebral perfusion pressure and osmolarity. It also showed to be effective in refractory intracranial hypertension, in situations where mannitol fails to lower ICP. Mannitol was less studied but demonstrated a higher incidence of mortality than HTS. There were several studies that did not report monitoring outcomes associated with serum osmolarity, despite the use of hyperosmolar therapies. Discrepancies were noticed between the studies in the overall study design in addition to reported monitoring parameters and length of stay. Conclusions: HTS seems to be safe and efficient in the treatment of severe TBI in children. The reduced existing studies regarding the use of mannitol do not permit a strong decision to be made concerning its practice. For the time being, the choice of hyperosmolar therapy in this context must be individualized and based on clinical practice and experience, not disregarding the latest guidelines that recommend the use of HTS.